2021
DOI: 10.3390/diagnostics11112042
|View full text |Cite
|
Sign up to set email alerts
|

Mesonephric-like Adenocarcinoma of the Uterine Corpus: Comprehensive Immunohistochemical Analyses Using Markers for Mesonephric, Endometrioid and Serous Tumors

Abstract: Mesonephric-like adenocarcinoma (MLA) of the uterine corpus is a rare but distinct malignant tumor of the female genital tract, demonstrating a characteristic morphology and unique immunohistochemical profiles and molecular alterations. We conducted immunohistochemical staining (IHC) to make precise differential diagnoses of uterine MLAs from common histological subtypes of endometrial carcinomas. We collected 25 uterine MLAs and performed IHC for GATA3, TTF1, CD10, ER, PR, p16, p53, and HER2. Seventeen cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(71 citation statements)
references
References 58 publications
2
69
0
Order By: Relevance
“…Our results of consistent GATA3 immunostaining in all cases corroborated the previous data. Regarding hormonal receptors, similar to previous studies, our ovarian MLA cases rarely showed ER and PR expression with weak-to-moderate staining intensity [ 39 , 40 , 41 , 42 ]. Even though it can be confusing to differentiate MLA from EC with the assumption of the low specificity of ER and PR, low-grade EC mimicking MLA would exhibit well-differentiated tubules or ductal structures showing uniform and strong expression for both ER and PR.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results of consistent GATA3 immunostaining in all cases corroborated the previous data. Regarding hormonal receptors, similar to previous studies, our ovarian MLA cases rarely showed ER and PR expression with weak-to-moderate staining intensity [ 39 , 40 , 41 , 42 ]. Even though it can be confusing to differentiate MLA from EC with the assumption of the low specificity of ER and PR, low-grade EC mimicking MLA would exhibit well-differentiated tubules or ductal structures showing uniform and strong expression for both ER and PR.…”
Section: Discussionsupporting
confidence: 90%
“…Pors et al [ 9 ] also reported the 5-year PFS of 43 uterine MLA patients as 27.5%. We also recently demonstrated that 64% (16/25) of uterine MLA patients were diagnosed as having stage III–IV tumors, and 18 (72%) patients experienced post-operative recurrences [ 39 ]. Taken together, we prudently assume at least that ovarian MLA might present as a relatively early-stage disease and more favorable prognosis than uterine MLA which is known to exhibit very aggressive clinical behavior and dismal prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Five of the six examined patients showed negative estrogen-receptor expression, and progesterone receptor was absent in all six examined patients. Despite the small number of examined patients, the positive rates of mesonephric markers and hormone receptors was similar to that observed in uterine MLA [ 24 ]. Information on TP53 mutation was available only in our case.…”
Section: Discussionsupporting
confidence: 73%
“…to distinguish uterine MLA from more commonly encountered histological types of endometrial carcinoma, including endometrial endometrioid carcinoma (EC) (10), serous carcinoma (SC), and carcinosarcoma (CS). A unique immunophenotype of MLA has also been documented in the literature (2,6,13,14). The following expression patterns support the diagnosis of MLA: positive immunoreactivities for mesonephric markers, including GATA-binding protein 3 (GATA3), paired box 2 (PAX2), transcription termination factor 1 (TTF1), and cluster of differentiation 10 (CD10); negative or only focal expression of hormone receptors; non-diffuse p16 positivity; and wild-type p53 immunostaining pattern (1,2,5,6,8,9).…”
mentioning
confidence: 80%
“…A unique immunophenotype of MLA has also been documented in the literature (2,6,13,14). The following expression patterns support the diagnosis of MLA: positive immunoreactivities for mesonephric markers, including GATA-binding protein 3 (GATA3), paired box 2 (PAX2), transcription termination factor 1 (TTF1), and cluster of differentiation 10 (CD10); negative or only focal expression of hormone receptors; non-diffuse p16 positivity; and wild-type p53 immunostaining pattern (1,2,5,6,8,9). Molecular studies using targeted next-generation sequencing (NGS) revealed that patients with uterine MLA frequently harbor a pathogenic mutation in the Kirsten rat sarcoma viral oncogene homolog (KRAS) gene, as well as alterations in neuroblastoma viral oncogene homolog, AT-rich interaction domain (ARID1A), phosphatidylinositol-4,5bisphosphate 3-kinase catalytic subunit alpha (PIK3CA), βcatenin, patched 2, and tumor protein 53 (TP53) (1,8,9,15).…”
mentioning
confidence: 80%